PENGARUH PENDIDIKAN KESEHATAN TERHADAP SIKAP CAREGIVER DALAM MENCEGAH PENULARAN TUBERKULOSIS PADA ANGGOTA KELUARGA - Sri Nur Hartiningsih; Anna Nur Hikmawati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2018)
ABSTRACTBackground: Millions of people die cause of tuberculosis in every year both in the world and in Indonesia. Tuberculosis attacks a lot in the productive age, so this can affect not only the patient himself but also the family which is to reduce family income. Various strategies and efforts have been made to reduce the incidence of TB, one of which is health education. Disease prevention will involve health education activities to increase public awareness about the importance of healthObjective: This study aims to determine the effect of health education on the caregiver's attitude in preventing tuberculosis in family members.Methods: The study uses the Quasy Experiment approach and the design of one group pretest-posttest with control group design. This research was conducted in 2 Puskesmas in Bantul Regency, with a sample of 30 respondentsResults: The results of this study used Paired t-test sample p 0.05 in the intervention group showed the attitude of p = 0,000 in the control group showed an attitude of p = 0,000.Conclusion: These results can be concluded that there is an influence of health education with audiovisual media and booklet media can improve the caregiver's attitude in preventing tuberculosis in family members.